Exploring the effects of hotel development, economic growth and exchange rate on tourism industry : evidence for Iran - Khanalizadeh, Bahman (Array, 2019)
The Purpose. This study is to investigate factors affecting the attraction of international tourists to Iran for the years 1983 to 2015. Design/Methodology/Approach. In this article, we examine using Autoregressive Distributed Lag (ARDL) method to explore the estimating the impacts of economic growth, hotel development, real exchange rate on tourism industry. Findings/Implications. The results of this study showed that the effect of all variables hotel development, merchandise trade, real exchange rate and real gross domestic product on international tourism In Iran, in the long-term and short-term positive and also bilateral relationship is between them. Also, the greatest impact on the increase in the number of tourists entering Iran is the real effective exchange rate and real GDP and a very important point that the results of this research show is that the development of hotels can increase both the short and long term of the number of international tourism to Iran, so in this regard, the development of the necessary technologies to increase this industry should be It will be on the agenda of the private and public sector of Iran. Originality. Given the increasing number of international tourists and the growing role of the tourism industry in the economies of the country, identification of effective factors in attracting international tourists is more than necessary. Governments and the private sector need to identify the factors affecting the tourism industry in order to develop, compete and survive in the tourism industry.